Blockchain in Swift : decentralized iOS programming - Karimov, Elshad (Apress, 2019)
"Implement Blockchains in iOS applications using the Swift programming language while working with the basics of blockchain development. In the first part of this video, the logic behind blockchains will be explained and then the same logic will be implemented in iOS application development. You'll work to develop a sample application where you'll allocate two accounts which will have a certain amount of bitcoins in them. Then you'll transfer those bitcoins between those accounts using blockchain technology by clicking transfer buttons in the application."--Resource description page